2015
DOI: 10.1016/j.jece.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Removal of dissolved humic acid from water by coagulation method using polyaluminum chloride (PAC) with calcium carbonate as neutralizer and coagulant aid

Abstract: The increasing global competition within today's manufacturing industries is confronting organizations with interdisciplinary challenges that require intellectual expertise and innovative technological solutions in various knowledge areas. Research organizations and manufacturing companies can improve their overall performance by bundling expertise in collaborative innovation networks. For this purpose a systematic Benchmarking approach has been developed by Fraunhofer IPK to match the competencies and capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…According to the results reported by Sudoh et al ., in comparision with aluminum sulfate (AS) and ferric chloride (FC), polyaluminum chloride (PAC) shows better efficiency of coagulation agents in HA removal. They concluded that PAC has large molecular weight, and therefore, it produces a huge amount of aluminum hydroxides.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results reported by Sudoh et al ., in comparision with aluminum sulfate (AS) and ferric chloride (FC), polyaluminum chloride (PAC) shows better efficiency of coagulation agents in HA removal. They concluded that PAC has large molecular weight, and therefore, it produces a huge amount of aluminum hydroxides.…”
Section: Resultsmentioning
confidence: 99%
“…They are able to react with chlorine and produce harmful compounds in water and make complex with heavy metals in water . Different tertiary methods such as active carbon adsorption , coagulation , membrane filter , sonochemical , photo‐Fenton process , and electrochemical oxidation are used by researchers to remove HAs compounds from wastewater. These processes are not attractive for industrial‐scale application because of high capital and operation costs.…”
Section: Introductionmentioning
confidence: 99%
“…In drinking water treatment, polyaluminum chloride, aluminum sulfate and ferric chloride are commonly used metal salt coagulant. Many studies have proposed that coagulation procedures can be used to remove humic acid [1]. Humic acid contains an aromatic heterocyclic structure.…”
Section: Introductionmentioning
confidence: 99%